Endoscopic multimodal imaging in Barrett's oesophagus - Mannath, Jayan (2013)
The incidence of oesophageal adenocarcinoma (OA) has increased exponentially in the western world over the past few decades. Barrett's oesophagus (BO) is a well known precursor of OA with a risk approximately 20 times more than that of background population. Regular endoscopic surveillance in patients with BO is recommended by most of the national gastroenterological societies. The advantage of Barrett's surveillance is to identify early subtle lesions which could then be managed early to avoid symptomatic and advanced cancers. The detection of such early lesions are challenging as they could be flat and inconspicuous on routine endoscopic examination. In the absence of any lesions, four quadrant biopsies every 1-2 cm of the whole length of Barrett's oesophagus is advised. This technique would map only 5-10% of the surface area of Barrett's segment and hence it is associated with significant sampling error. The improvement in electronics over the past decade has led to the production of endoscopes with better charged coupled devices and image enhancement techniques by altering the spectrum of light.